How South Bangla Agriculture and Commerce Bank Ltd. minimizes their risk level in case of different loan categorizes - Ahmed, A.M. Tamim (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.